Conformation and anticancer activity of a novel mannogalactan from the fruiting bodies of Sanghuangporus sanghuang on HepG2 cells. (June 2022) - Cheng, Junwen; Song, Jiling; Wang, Yanbin; Wei, Hailong; He, Liang; Liu, Yu; Ding, Hongmei; Huang, Qingrong; Hu, Chuanjiu; Huang, Xubo; Jiang, Yihan; Wu, Youliang
Graphical abstract: Highlights: A mannogalactan was isolated from the fruiting body of Sanghuangporus sanghuang . Its backbone had 1, 6-linked α-D-Man p, 1, 6-linked α-D-Gal p and α-D-3- O -Me-Gal p. The Ra and Rq of HepG2 cell surface increased dramatically after SSPS1 treatment. It could induce HepG2 cells apoptosis via the mitochondrial pathway. Abstract: A novel water-soluble mannogalactan (SSPS1) with an average molecular weight of 2.04 × 10 4 Da was obtained from the fruiting bodies of the Sanghuangporus sanghuang . It revealed that SSPS1 was composed of d -galactose, d -mannose, l -fucose, 3- O -methylgalactose and d -glucose in a ratio of 6.2:3.9:3.1:2.1:1.0. The structural elucidation of SSPS1 consisted of 1, 6-linked α-D-Gal p, 1, 6-linked α-D-Man p and 1, 6-linked 3- O -methyl-α-D-Gal p backbone with branching at O -2 of 1, 6-α-D-mannosyl residues by α-L-Fuc p and α-D-Glc p units. The conformational parameters suggested that a flexible chain conformation of SSPS1 in solution based on light scattering and atomic force microscopy imaging. Intriguingly, it presented potent anticancer activity on HepG2 cell with Rq and Ra values increased dramatically up to 73.93 nm and 53.92 nm compared with the control. The analysis of flow cytometry indicated SSPS1 could induce the apoptosis of HepG2 cells and arrest them via S phase. Western blot assay further uncovered that apoptosis process was triggered by SSPS1 via a mitochondria-mediated signaling pathway, which was evidenced by an increased ratio of Bax/Bcl-2, the release of cytochrome c and the strong activation of caspase-3 and 9. Taken together, these results suggested that SSPS1 might be applied in functional food as an anticancer agent.